Innovations in Agricultural Bio-Inputs: Commercial Products Developed in Argentina and Brazil - da Silva Medina, Gabriel (2024)
Innovations in agricultural bio-inputs can lead to sustainable alternatives to replace synthetic fertilizers and pesticides. However, there is no clear understanding of what technologies can become available to farmers as commercial products, particularly in developing countries. This study summarizes the innovations used in commercial products in Argentina and Brazil based on the countries’ official data and on in-depth surveys conducted with 14 bio-input private companies. The results reveal ongoing development efforts to improve traditional products, such as inoculants that help plants fix nitrogen. There is also progress in mastering the formulation of new bio-inputs, such as bio-fertilizers that promote plant growth and biopesticides for pest control. Lastly, the next generation of bio-inputs composed of hytovaccines promises to help prepare plants’ immune systems against the attack of pathogenic fungi and bacteria, while bio-herbicides can potentially reduce the use of synthetic herbicides to prepare fields for harvest. Domestic companies based in Argentina and Brazil play an important role in these innovations that can underpin bio-economy growth in developing countries.